The effect of COVID-19 on the gender gap in remote work - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2024)
We examine changes in the gender gap in working from home (WFH) in response to the unanticipated first wave of the COVID-19 pandemic. Using data from the American Time Use Survey, we find a non-negligible widening of the gender gap with WFH being more prevalent among women than among men. Respondents' job traits played a significant role in the gender gap variations, those working in the private sector being the most affected. Young individuals, those more educated, and those living with a dependent person increased the gender gap more in terms of the proportion of time devoted to WFH. We further show evidence suggesting the mitigating effect of non-pharmaceutical interventions during the first wave of the pandemic, positively affecting the WFH tendency for men but not for women. Overall, the gender gap change proves robust to identification checks. In addition, the gender gap response has had a long-lasting impact on the gender gap.
Keywords: D10; J16; J21; J22; 330; COVID-19; working from home (WFH); gender; American Time Use Survey (ATUS)